Unveiling The Dynamic Power Of Gamification In Student Learning Through Novel Conceptual And Theoretical Frameworks - Mohammed El Messaoudi; Mohammed Larouz (The Journal of Studies in Language, Culture and Society)
This research paper endeavours to construct a comprehensive conceptual and theoretical framework for gamified learning, with the aim of exploring the potential of game-based approaches in education to enhance student engagement. Through an extensive literature review and analysis of relevant theoretical perspectives, this study develops a robust framework that elucidates the fundamental concepts, relationships, and mechanisms involved in gamified learning. By establishing this theoretical foundation, a deeper understanding of the principles and processes of gamification in education is achieved, offering valuable insights into effective strategies for implementing gamified approaches to optimize student engagement and improve educational outcomes. Drawing from existing knowledge, this research identifies key factors that contribute to successful gamified learning experiences and provides practical recommendations for educators, policymakers, and researchers seeking to harness the power of gamification to transform educational practices. This study aims to unlock the untapped potential of gamification in education by bridging the gap between theory and practice, making significant contributions to the enhancement of student engagement and the improvement of educational outcomes through innovative pedagogical approaches.